Seasonal changes in muscle structure and flesh quality of 0+ and 1+ Atlantic salmon (Salmo salar L.): impact of feeding regime and possible roles of ghrelin. (2nd April 2012) - Johnsen, C.A.; Hagen, Ø.; Solberg, C.; Björnsson, B.T.H.; Jönsson, E.; Johansen, S.J.S.; Bendiksen, E.Å.
Abstract Growth performance, muscle cellularity, flesh quality, and plasma ghrelin were investigated in 0+ and 1+ farmed Atlantic salmon (Salmo salar L.) from 40 g to 4.3 kg. Reduced meal frequency was introduced in both smolt groups from 1.5 kg; one meal per second day (<5 °C) to one daily meal (>5 °C), while control groups were fed one to three daily meals. Results show that 0+ salmon had higher final fibre number and density, pigment content, red colour intensity, firmer flesh, and lower fillet fat content than 1+ salmon at 4.3 kg, affected by season and smolt type. Muscle fibre recruitment was an important determinant of fillet firmness and colour, possibly influenced by the prenatal temperature regime. Fish fed reduced meal frequency showed temporal reduced feeding ration, but growth performance was not compromised in any smolt groups at harvest. However, fillet fat, gaping, and colour decreased by less frequent feeding, with permanent effects in 1+ salmon for gaping and fat. Reduced meal frequency is therefore considered to be a promising tool for managing important flesh quality attributes in salmon without compromising growth performance. It is also suggested that ghrelin stimulates short‐term appetite, and perhaps also in the longer term.